Simple separation and characterization of lanthanide–polyaminocarboxylic acid complexes by HILIC ESI-MS. Issue 113 (29th October 2015) - Beuvier, L.; Bresson, C.; Nonell, A.; Vio, L.; Henry, N.; Pichon, V.; Chartier, F.
Abstract : Lanthanide complexes with EDTA and DTPA ligands were separated and characterized by HILIC ESI-MS for the first time. Abstract : The separation and characterization of lanthanide (Ln) complexes bearing ethylenediaminetetraacetic acid (EDTA) and diethylenetriaminepentaacetic acid (DTPA), species of concern in advanced nuclear fuel treatment processes, were investigated by hydrophilic interaction liquid chromatography (HILIC) coupled with electrospray ionization mass spectrometry (ESI-MS). Selectivity properties of stationary phases with different polar functions (cross-linked diol, cyano, zwitterionic and amide) towards the Ln (Er, Eu, Gd, Nd)–EDTA/DTPA complexes were assessed. Only amide bonded stationary phases allowed simple separation of the complexes in isocratic mode, while the other stationary phases did not provide sufficient selectivity, leading to the co-elution of the complexes whatever the mobile phase composition. The chromatographic properties of two amide-based columns with different surface characteristics (XBridge and TSK Gel) were probed with a set of lanthanide complexes under identical conditions. The column giving the best performances was selected for further retention mechanism study. The effect of several parameters, such as the acetonitrile (ACN) content (40–80%) and ammonium acetate concentration (5–20 mmol L −1 ) was studied on the retention of the lanthanide complexes. The results showed that electrostatic interactions did not significantly affect their elution, while the adsorption mechanism was found to be predominant for ACN percentages higher than 55%. In the final step, faster HPLC conditions were applied by using an amide column packed with sub-2 μm particles (Acquity). More efficient separation of the lanthanide complexes, and decreases in analysis time, solvent consumption and generated effluent volumes, were obtained. Such an approach could lead to the development of greener analytical methods than conventional chromatographic separations, which is of prime concern for the study of radioactive samples.